2013
DOI: 10.48550/arxiv.1309.6561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boundary Values Properties of Functions in Weighted Hardy Spaces

Abstract: In this paper we study the boundary values of harmonic and holomorphic functions in the weighted Hardy spaces on the unit disk D. These spaces were introduced by Poletsky and Stessin in [6] for plurisubharmonic functions on hyperconvex domains D ⊂ C n as generalizations of classical Hardy spaces. We show that in the case when D is the unit disk D the theory of boundary values for functions in these spaces is analogous to the classical one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…M. A. Alan and N. G. Goguş in [1], S. S ¸ahin in [10] and K. R. Shrestha in [9] have independently produced examples that in general these new spaces H p u (D) do not coincide with the classical spaces H p (D). They have found an exhaustion funcion u for which H p u (D) H p (D).…”
Section: Basic Factsmentioning
confidence: 99%
See 2 more Smart Citations
“…M. A. Alan and N. G. Goguş in [1], S. S ¸ahin in [10] and K. R. Shrestha in [9] have independently produced examples that in general these new spaces H p u (D) do not coincide with the classical spaces H p (D). They have found an exhaustion funcion u for which H p u (D) H p (D).…”
Section: Basic Factsmentioning
confidence: 99%
“…Recently these spaces were subjected to more detailed studies in [1,9,10] when D is the unit disk D. The main goal of these papers was to establish properties of weighted Hardy spaces similar to the standard properties of the classical Hardy spaces. In this paper we continue this program looking more thoroughly at the properties of boundary values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, M. Alan and N. Gogus in [1], S. Sahin in [9] and K. R. Shrestha in [10,11] obtained the description of these spaces on the unit disk and called them Poletsky-Stessin Hardy spaces. In particular, they showed that the new spaces form a subclass of weighted Hardy spaces introduced at the beginning of this section.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, M. Alan and N. Gogus in [1], S. Sahin in [14], K. R. Shrestha in [16] and the latter with the author in [11] showed that if D is the unit disk D these spaces form a subclass of weighted Hardy spaces studied, for example, in [8] and [3]. However, these subclass has special properties and, moreover, has no analogs in several variables.…”
Section: Introductionmentioning
confidence: 99%